Preparation and characterization of polylactic acid/ poly (ԑ-caprolactone) /clay/ oil palm mesocarp fiber hybrid composite - Eng, Chern Chiet (2014)
The research focused on incorporation of Oil Palm Mesocarp Fiber (OPMF) as filler in polylactic acid/poly(ε-caprolactone) (PLA/PCL) blends. The addition of clay as compatibilizer to improve mechanical and thermal properties of the composites. OPMF was bleached and then treated with silane coupling agent due to incompatibility of hydrophilic OPMF with hydrophobic matrix. PLA/PCL blends were prepared by melt blending technique with the best ratio is 85/15. Fourier transform infrared (FTIR) revealed that there is physical interaction between PLA and PCL in blends. Thermogravimetric Analysis (TGA) showed that degradation of blends is two steps. Dynamic Mechanical Analysis (DMA) showed that blends exhibit two glass transition temperature (Tg) which indicated PLA/PCL is immiscible. The PLA/PCL/clay composites were prepared by melt intercalation technique. X-ray diffraction (XRD) showed shifting of diffraction peak while transmission electron microscopy (TEM) indicated formation of agglomerate when clay was added. The addition of clay Nanomer® PGV makes blends become more flexible while addition of clay Montmorillonite K10 makes blends become stiffer. TGA thermograms proved that the presence of clay improve thermal stability of blends. Loss modulus shows that the addition of clay shifts two Tg in composites become closer to each other. Scanning electron microscopy (SEM) micrograph revealed that clay Nanomer® PGV composites is more homogeneous and appear as single phase morphology. The effect of 1% clay Nanomer® PGV on PLA/PCL/OPMF biocomposites was investigated. FTIR spectra showed that there is physical interaction between PLA, PCL, clay and OPMF in composites as peak shifting is observed. The addition of clay improves mechanical properties of biocomposites. TGA thermograms revealed that the addition of clay improves the thermal stability of the biocomposites. Loss modulus shows that the addition of clay shifts two Tg in composites become closer to each other and low tan δ indicate better fiber/matrix adhesion. SEM micrograph showed the addition of clay improves fiber/matrix adhesion as fiber breakage on the fracture surface. FTIR spectra showed that bleaching of OPMF successfully removes hemicellulose from fibers while silanized unbleached and silanized bleached OPMF are less hydrophilic. Silanized bleached OPMF composites showed best mechanical properties in PLA/PCL/clay/OPMF hybrid composites. FTIR spectra indicated there is interaction between both silane treated OPMF with matrix. DMA showed that both silane treated OPMF shift two Tg in composites become closer while low tan δ peak show good fiber/matrix adhesion of bleached silane treated OPMF composites. SEM micrograph indicated that better adhesion between silanized bleached fiber with matrix as fiber breakage in the fracture surface. Water sorption test showed that silanized bleached OPMF is most water resistance with less water uptake.